PENGARUH PERMAINAN MATH EKSPLORATIF BOX TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA 1 PEKANBARU - Nur Alia Fitri; Zulkifli N; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this research is to find out the effect pf math explorative box game on the ability to recognize the concept of numbers. The population in this study was 4-5 years old at TK Negeri Pembina 1 Pekanbaru. The sample in this study wasgroup A totaling 20 children. Data collection uset in this study was bay pretest and posttest observation. Data analysis techniques in the study used the t test using SPSS 17.This metode research was an experimental study using the design of one group pretest posttest design.based on the analysis data and the results of the percentage of the effects that are significant, it can be seen from the result of the petest (before implementation) taht a value of 115 is obtained with an average of 5,75.Then do an experiment using the meth explorative box game, so that the posttest is 163 with an average of 8,15. To find out how much the influence of math explorative box games on childred aged 4-5 years in TK Negeri Pembina 1 Pekanbaru is 38,4% and 57.82% influence other factors.Key Words: Math Explorative Box Game, Concept Of Numbers